Principle-Centred Leadership - Covey, Stephen (Simon & Schuster UK Ltd, 1992)
The author invites people to centre their lives and leadership around such timeless principles as fairness, equity, justice and integrity that constitute the roots of every family and institution that has ever prospered.
Keywords: Inspirational; Leadership; Non Fiction; Self Improvement